Efektifitas Penggunaan Media Pembelajaran Nearpod Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas VII Materi Suhu Dan Kalor - Nor Hidayah Dayah; Ratna Yulinda; Sauqina (CV.ITTC INDONESIA, 2026)
Learning in the modern era of the 21st century requires students to deepen various important skills, including critical thinking skills. Initial findings indicate that students' critical thinking skills are still relatively low, with an average of only 34.35%. Seeing this situation, this study was conducted with the following objectives: (1) to evaluate the effect of using Nearpod learning media on improving students' critical thinking skills on the topic of temperature and heat; and (2) to describe the level of students' critical thinking skills after participating in interactive media-based learning, namely Nearpod. The study was conducted using a quasi-experimental approach with a Non-Equivalent Control Group Design, two classes were selected, one as an experimental class and one as a control class in grade VII students of MTsN 2 Banjar. Data were collected through a critical thinking skills test and analyzed using ANCOVA (Analysis of Covariance). The results of the analysis showed that: (1) The use of Nearpod learning media had a very positive effect on the development of students' critical thinking skills. The results of the ANCOVA analysis showed a significance result of 0.000 (<0.05), which confirmed that the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. The average score of students' critical thinking skills in the class that implemented Nearpod media reached 78.28, higher than the score of 66.25 in the class that did not implement the media. This finding shows a significant difference in students' critical thinking skills from seventh grade science subjects, on the topic of temperature and heat. 2) Nearpod media is equipped with interactive features, such as interesting and easy-to-understand learning videos related to the concepts of temperature and heat, as well as virtual PhET simulations that can be accessed directly through students' mobile devices. These features encourage students to think